A kind of basic anion exchange membrane and preparation method thereof

By combining imidazolium salt crystals with metal organic frame crystal materials and chloromethylated block polymers in the alkaline anion exchange membrane, the existing membranes are solved in a high-temperature alkaline environment. The problem of easy degradation achieves both high stability and high ion conduction performance.

CN115521568BActive Publication Date: 2025-01-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210872320.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-20
Publication Date
2025-01-14
Estimated Expiration
2042-07-20

AI Technical Summary

Technical Problem

The existing alkaline anion exchange membranes are prone to degradation in high-temperature alkaline environments, resulting in a decrease in ion conductivity and short service life, making it difficult to ensure high stability and high ion conductivity at the same time.

Method used

Imidazolium salt crystals are combined with metal organic frame crystal materials and chloromethylated block polymers, and synthesized by low-temperature vacuum method and cross-linking to form an anion exchange membrane with a high serialization structure to ensure that the imidazolium salt is in metal. It exists stably in the organic frame, enhancing the mechanical strength and chemical stability of the membrane.

Benefits of technology

It improves the ion conductivity and mechanical strength of the anion exchange membrane, extends the service life, and maintains good electrochemical performance and durability in an alkaline environment, reducing swelling problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure GDA0003898780020000041
    Figure GDA0003898780020000041
Patent Text Reader

Abstract

The present invention belongs to the field of anion exchange membranes, and relates to a basic anion exchange membrane and a preparation method thereof. The basic anion exchange membrane is composited by imidazolium salt crystals, chloromethylated block polymers and crosslinking agents, wherein the synthesis of imidazolium salt crystals uses a low-temperature vacuum method to fix a substance formed by using 4,5-disubstituted imidazolium salts as raw materials in a metal organic framework crystal material; the preparation of the basic anion exchange membrane is by blending the chloromethylated block polymer and the imidazolium salt crystals to form a blended solution, then adding a crosslinking agent to form a casting solution, and the prepared ion exchange membrane is alkalized and dried to form a basic anion exchange membrane. The basic anion exchange membrane of the present invention effectively reduces swelling by covalent crosslinking, improves membrane chemical durability and alkali stability; the addition of imidazolium salts constructs a rich and orderly ion transmission channel in the membrane, reduces ion transmission resistance, and improves the ion conduction capacity of AEMs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an alkaline anion exchange membrane and a preparation method thereof, belonging to the field of anion exchange membranes. Background Art

[0002] Polymer electrolyte membrane fuel cells are a clean and efficient energy technology that can be used as a backup power source for buildings, engine power sources, and portable power lamps, and have broad application prospects. Polymer electrolyte membrane fuel cells can be divided into proton exchange membrane fuel cells (PEMFCs) and alkaline anion exchange membrane fuel cells (AEMFCs). Compared with PEMFCs, the electrode reaction kinetics of AEMFCs are faster, non-precious metal catalysts can be used, the use of precious metal catalysts such as Pt is avoided, and the cost of fuel cells is reduced. In addition, in an alkaline environment, the stability of the catalyst is greatly improved. Therefore, AEMFCs have received increasing attention.

[0003] Anion exchange membranes (AEMs) are one of the core components of alkaline anion exchange membrane fuel cells, and largely determine the performance and life of the battery. AEMs should have advantages such as high ion conductivity and good alkaline stability to meet the requirements of fuel cell operation. In recent years, many researchers have improved membrane materials in the hope of meeting the requirements of fuel cell use. However, the operating life and stability of AEMs in batteries still face major challenges.

[0004] First, many scholars have improved the stability of AEMs by developing stable ion-conducting groups, mainly including quaternary ammonium, imidazole, guanidine, metal complex cations, etc. Because these ion-conducting groups are positively charged, they are easily attacked by nucleophilic hydroxide ions under alkaline conditions, resulting in nucleophilic substitution, Hofmann degradation, or the formation of ylide intermediates, inducing chemical rearrangement. By reducing electron-withdrawing groups and increasing electron-donating groups accordingly, the electron density of ion-conducting groups is increased to increase the steric hindrance of electron-deficient positions, which can reduce the attack of hydroxide ions and improve the stability of ion-conducting groups. However, the stability of the main chain structure of AEMs seriously affects its service life, and the chemical degradation of the main chain structure leads to irreversible damage to AEMs.

[0005] Secondly, the stability of AEMs is increased by optimizing the connection mode between the ion-conducting group and the polymer main chain. In the study of AEMs, it was found that the hydroxide ion-conducting group is mainly connected to the polymer main chain structure in the form of benzyl. In a strong alkaline environment, especially at 80°C, the stability of the benzyl group is poor and it is easy to be attacked by the nucleophilic hydroxide ion, resulting in the loss of ion exchange capacity and hydroxide ions. In recent years, the research work has mainly been to introduce long chains between the ion-conducting group and the polymer main chain, so that the ion-conducting group is far away from the benzene ring and other structures of the polymer main chain, especially the unstable main chain structures such as amines and carbonyl groups. Although this method can solve the stability problem of the ion-conducting functional group to a certain extent, in the complex reaction environment of the fuel cell, especially the generation of active factors such as free radicals, the ion exchange membrane still inevitably splits and degrades, seriously affecting its service life.

[0006] Of course, in view of the above two solutions, most researchers still improve the stability of anion exchange membranes by designing a polymer main chain structure with good stability. The representative compound polyarylether is one of the research hotspots. Polyarylether has the advantages of good thermal stability, high mechanical strength, and easy modification, and has been widely studied in AEMs. However, with the deepening of research, it was found that the introduction of ion-conducting groups would reduce the stability of such main chains, making them susceptible to attack by hydroxide ions and chain breaking. In an alkaline environment, many single-structure compound main chains have many disadvantages, so attempts were made to design a polymer main chain structure connected by multiple compounds. This type of polymer main chain structure greatly improves stability due to the superposition of its own multiple properties, but the resulting reduction in ion conductivity reduces the use effect.

[0007] In view of the above, how to design and prepare anion exchange membranes with high ion conductivity and high stability is currently the most important task. Summary of the invention

[0008] The purpose of the present invention is to provide an imidazole crystal type alkaline anion exchange membrane and a preparation method thereof, aiming to solve the defect that the anion exchange membrane is easy to degrade, thereby ensuring the high stability of the anion exchange membrane while also having high ion conductivity.

[0009] The above technical purpose of the present invention is achieved through the following technical solutions:

[0010] On one hand, the present invention provides an imidazole crystal-type alkaline anion exchange membrane, which is composited by imidazolium salt crystals, chloromethylated block polymers and a crosslinking agent, wherein the imidazolium salt crystals are: a substance formed by using 4,5-disubstituted imidazolium salt as a raw material and fixed in a metal organic framework crystal material; the 4,5-disubstituted imidazolium salt is a 1-butyl C4, C5 disubstituted imidazolium salt or a 1-hexyl C4, C5 disubstituted imidazolium salt.

[0011] In the above technical solution, further, the raw material of the imidazolium salt crystal also includes p-chloromethylstyrene.

[0012] In the above technical solution, further, the metal organic framework crystal material is a cubic structure with micropores, the pore size of the micropores is 100-1000nm, and the metal organic framework crystal material is one or more of MIL-101 (Fe), MIL-101 (Cr), MIL-53 (Cr), MIL-53 (Fe), ZIF-6, ZIF-8, and ZIF-10;

[0013] The chloromethylated block polymer is one or more of styrene-butylene block copolymer (SBS), styrene-ethylene-butylene block copolymer (SEBS), acrylonitrile-butadiene-styrene copolymer (ABS), acrylonitrile-ethylene-styrene copolymer (AES), acrylonitrile-styrene copolymer (AS), acrylonitrile-styrene-acrylate copolymer (ASA), wherein the styrene block content is 10-57wt.%;

[0014] The cross-linking agent is one or more of N,N,N',N'-tetramethylmethanediamine (TMMDA), N,N,N',N'-tetramethylethylenediamine (TMEDA), and N,N,N',N'-tetramethyl-1,6-hexanediamine (TMHDA).

[0015] In the above technical solution, further, the imidazolium salt crystal is synthesized by a low-temperature vacuum method, and the C4 and C5 disubstituted imidazolium salts are reacted with other raw materials to be "fixed" in the crystal material of the metal organic framework material with a microporous cubic structure, comprising the following steps:

[0016] (1) placing a metal organic framework crystal material having a microporous cubic structure in a Schlenk tube equipped with a constant pressure funnel, and continuously evacuating the metal organic framework crystal material to place it in a vacuum state;

[0017] (2) under low temperature environment, mixing a mixture of 4,5-disubstituted imidazolium salt and p-chloromethylstyrene with a metal organic framework crystal material, stirring and reacting, so that the 4,5-disubstituted imidazolium salt reacts with p-chloromethylstyrene;

[0018] (3) After the reaction is completed, centrifugation is performed to allow the vinyl groups in the chloromethylstyrene to self-crosslink and obtain imidazolium salt crystals.

[0019] In the above technical scheme, further, the vacuum degree of the vacuum state in step (1) is -0.6 to -1.0 MPa; the low-temperature reaction temperature in step (2) is -20 to -10°C, and the stirring time is 48-96 hours; the molar ratio of the metal organic framework crystal material to the imidazolium salt to p-chloromethylstyrene is 1:2:0.5-5; the precipitate drying temperature in step (3) is 60-100°C, and the drying time is 4-8 hours; steps (1) and (2) are in the same vacuum state.

[0020] In the above technical solution, further, the C4 and C5 substituents in the 1-butyl C4, C5 disubstituted imidazolium salt or the 1-hexyl C4, C5 disubstituted imidazolium salt are R1 and R2 respectively, and the R1 and R2 are any one of methyl, ethyl, propyl, butyl, isopropyl, and tert-butyl. The structures of the 1-butyl C4, C5 disubstituted imidazolium salt or the 1-hexyl C4, C5 disubstituted imidazolium salt are as follows:

[0021]

[0022] Another aspect of the present invention provides a method for preparing the aforementioned alkaline anion exchange membrane, comprising the following membrane preparation steps:

[0023] A. Weigh the chloromethylated block polymer and dissolve it in a high boiling point solvent, and stir and dissolve it at room temperature to obtain a polymer solution; preferably, the high boiling point solvent is one of N-methylpyrrolidone, N,N-dimethylformamide, tetrahydrofuran, and dimethyl sulfoxide;

[0024] B. Add a crosslinking agent to the polymer solution prepared in step A, and continue to stir and dissolve at room temperature to obtain a mixture solution;

[0025] C. Weigh imidazolium salt crystals and add them to the mixture solution obtained in step B. Mix and heat to react to obtain a casting solution.

[0026] D. pouring the casting solution prepared in step C into a glass mold, and peeling the obtained film from the glass mold after drying;

[0027] E. Soak the membrane obtained in step D in an ethanol solution of 4,5-disubstituted imidazolium salt and then remove it;

[0028] F. Soak the membrane obtained in step E in an alkaline solution, then wash it with deionized water for more than 5 times, and dry it to obtain an imidazole crystal-type alkaline anion exchange membrane.

[0029] In the above technical scheme, further, the mass concentration of the polymer solution in step A is 0.5-2wt.%; the amount of the crosslinker added in step B is 0.1-0.5% of the mass of the chloromethylated block polymer; the amount of the imidazolium salt crystals added in step C is 2-10% of the mass of the chloromethylated block polymer; the mass concentration of the ethanol solution of the imidazolium salt crystals in step E is 1-5wt%, and the immersion time is 24-48h.

[0030] In the above technical solution, further, the mass concentration of the ethanol solution of 4,5-disubstituted imidazolium salt in step E is 1-5wt%, and the immersion time is 24-48h.

[0031] In the above technical scheme, further, the room temperature in step A and step B is 25°C, the stirring time in step A is 24-48h, the stirring time in step B is 10-120s, ultrasonic mixing is performed in step C, the heating temperature is 25-80°C, and the heating reaction time is 0.2-12h; the drying temperature in step D is 80-100°C, and the drying time is 24-48h; the drying temperature in step F is 60-80°C, and the drying time is 24-48h.

[0032] In the above technical solution, further, the alkaline solution in step F is one of sodium hydroxide or potassium hydroxide, the concentration of the alkaline solution is 0.1-2 mol / L, the soaking time is 24-48h, and the drying temperature is 50-60°C.

[0033] The present invention has the following beneficial effects:

[0034] 1. The anion exchange membrane of the present invention adopts imidazolium salt, metal organic framework crystal material, chloromethylated block polymer and crosslinking agent. First, in the synthesis of metal organic framework crystal material and imidazolium salt, the metal organic framework crystal material can provide a place for accommodating imidazolium salt and p-chloromethylstyrene, that is, the metal organic framework crystal material can be used as a container to load the functionalized compound-imidazolium salt and p-chloromethylstyrene, so that the imidazolium salt and p-chloromethylstyrene react to form a macromolecular structure, so that the imidazolium salt is firmly locked in the metal organic framework crystal material, so that the prepared anion exchange membrane will not cause chemical degradation of the ion membrane and loss of functionalized ion groups due to changes in the reaction environment; on the other hand, since the lattice structure of the metal organic framework crystal material in the imidazolium salt crystal is highly ordered, the imidazolium salt and other compounds with ion transport function can uniformly and orderly transport ions, which not only ensures the continuity and stability of ion transport, but also improves the mechanical strength and service life of the ion membrane;

[0035] In addition, by using the chloromethylated block polymer as the main support material and then using a cross-linking agent to carry out a cross-linking reaction to form a network structure, on the one hand, the imidazolium salt crystals are firmly wrapped in the polymer support material, and the imidazolium salt crystal loss and other problems will not occur, so the ion transmission efficiency can be stably maintained; on the other hand, the cross-linking agent used in the present invention also provides ion transmission functional groups after quaternization treatment, thereby improving the ion transmission efficiency of the membrane; further, the present invention uses a chloromethylated block polymer cross-linked polymer with excellent chemical stability as a skeleton, and after forming a cross-linked network structure through covalent cross-linking, the mechanical strength of the membrane is increased, and it is not easy to stretch after absorbing the solvent, thereby effectively reducing the swelling problem and improving the chemical durability of the membrane. The swelling degree of the composite membrane is reduced to less than 5%, and the membrane shows good alkali resistance stability through an alkali solution immersion test, while its ion conductivity is not weakened, and the electrochemical performance remains good;

[0036] 2. The anion exchange membrane of the present invention adopts the synthesis of metal organic framework crystal materials and imidazolium salts. By "fixing" crystals carrying "flowing" imidazolium salt small molecule conductive groups in the membrane, water is sucked into the membrane by utilizing the deliquescence of the imidazolium salts and the siphon effect of the nanoscale pores, and rich and orderly ion transmission channels are constructed in the membrane, reducing the ion transmission resistance, breaking through the number limit of covalently bound functional groups in the membrane, shortening the ion transmission path, reducing the ion transmission resistance, and improving the ion conduction capacity of AEMs, effectively avoiding the membrane swelling problem caused by the increase of groups;

[0037] 3. When C4 and C5 substituted imidazoles are used as functional groups in the present invention, due to the substituent effect and the hyperconjugation effect, a stable compound effect is formed, so that the chemical barrier for the hydroxide ion to attack the active site is increased, and the degradation effect on the membrane is effectively reduced; in addition, the alkane group itself has good stability in an alkaline environment and is not easily chemically degraded; on the other hand, the addition of the substituent group increases the overall steric hindrance of the polymer structure, and the hydroxide ion attack on the active site needs to break through a higher steric barrier. In summary, the present invention uses alkane substituents to effectively improve the stability of the composite membrane, and also lays a foundation for the research and development of highly stable AEMs;

[0038] 4. After preparing the anion exchange membrane, the present invention uses an alkaline solution to alkalize and functionalize it, in order to replace the chloride ions in the imidazolium salt structure with OH-, so that the composite membrane is fully alkaline and no chloride ions will poison the catalyst during use. DETAILED DESCRIPTION

[0039] The present invention is described in further detail below.

[0040] Embodiment 1:

[0041] (1) Weigh 6.99 g (0.01 mol) of MIL-101(Fe) and place it in a Schlenk tube equipped with a constant pressure funnel. Continuously evacuate the tube to maintain a vacuum degree of -1.0 MPa and lower the temperature of the Schlenk tube to -10°C.

[0042] (2) Weigh 3.04 g (0.02 mol) of 1-hexyl-4,5-dimethylimidazolium salt and 1.525 g (0.01 mol) of p-chloromethylstyrene, inject the mixture into the Schlenk tube of step (1), and continue stirring for 96 h to allow 1-hexyl-4,5-dimethylimidazolium salt to react fully with p-chloromethylstyrene;

[0043] (3) After the reaction is completed, the precipitate is centrifuged and then dried at 60° C. for 8 h to allow the vinyl groups to self-crosslink and form imidazolium salt crystals;

[0044] (4) At 25° C., 2 g of chloromethylated styrene-ethylene-butylene block copolymer with a styrene content of 10% was weighed and dissolved in 398 g of N-methylpyrrolidone. The mixture was stirred for 48 h, and then 0.002 g of N,N,N′,N′-tetramethylmethanediamine was weighed and added. The mixture was stirred thoroughly to dissolve for 10 s.

[0045] (5) Weigh 0.04 g of imidazolium salt crystals and add them to step (4), and continue stirring at 25° C. for 12 h to obtain a casting solution;

[0046] (6) heating the casting liquid obtained in step (5) in a glass mold at 60° C. for 96 h, and peeling the dried film from the glass plate for later use;

[0047] (7) Weighing 1.0 g of the imidazolium salt crystals prepared in step (3) and adding them to 99 g of ethanol to obtain an imidazolium salt ethanol solution with a concentration of 1%;

[0048] (8) The membrane obtained in step (6) is placed in the solution prepared in step (7), soaked for 48 hours, taken out, and repeatedly rinsed with deionized water for 10 times, and then soaked in a 0.1 mol / L sodium hydroxide solution to fully alkalize for 24 hours, and then taken out and rinsed off the alkaline solution on the surface of the membrane with deionized water, and then thoroughly dried at 60°C for 48 hours to obtain an imidazole crystalline alkaline anion exchange membrane.

[0049] Embodiment 2:

[0050] (1) Weigh 2.3 g (0.01 mol) of ZIF-8 and place it in a Schlenk tube equipped with a constant pressure funnel. Continuously evacuate the tube to maintain a vacuum degree of -0.6 MPa, and lower the temperature of the Schlenk tube to -20 °C.

[0051] (2) Weigh 3.04 g (0.02 mol) of 1-butyl-4,5-dimethylimidazolium salt and 1.525 g (0.01 mol) of p-chloromethylstyrene, inject the mixture into the Schlenk tube of step (1), and continue stirring for 48 h to allow 1-butyl-4,5-dimethylimidazolium salt and p-chloromethylstyrene to react fully;

[0052] (3) After the reaction is completed, the precipitate is centrifuged and then dried at 100° C. for 4 h to allow the vinyl groups to self-crosslink and form imidazolium salt crystals;

[0053] (4) At 25° C., 5 g of chloromethylated acrylonitrile-butadiene-styrene block copolymer with a styrene content of 30% was weighed and dissolved in 495 g of N-methylpyrrolidone, and stirred for 24 h. Then, 0.01 g of N,N,N′,N′-tetramethylethylenediamine was weighed and added, and stirred thoroughly to dissolve for 120 s.

[0054] (5) Weigh 0.25 g of imidazolium salt crystals and add them to step (4), and continue stirring at 25° C. for 0.2 h to obtain a casting solution;

[0055] (6) heating the casting liquid obtained in step (5) in a glass mold at 70° C. for 72 h, and peeling the dried film from the glass plate for later use;

[0056] (7) Weigh 3.0 g of the imidazolium salt crystals prepared in step (3) and add them to 97 g of ethanol to obtain an imidazolium salt ethanol solution with a concentration of 1%;

[0057] (8) The membrane obtained in step (6) is placed in the solution prepared in step (7), soaked for 36 hours, taken out, and repeatedly rinsed with deionized water for 10 times, and then soaked in a 1 mol / L sodium hydroxide solution to fully alkalize for 36 hours, and then taken out and rinsed off the alkaline solution on the surface of the membrane with deionized water, and then thoroughly dried at 70°C for 36 hours to obtain an imidazole crystalline alkaline anion exchange membrane.

[0058] Embodiment 3:

[0059] (1) Weigh 7.19 g (0.01 mol) of MIL-101(Cr) and place it in a Schlenk tube equipped with a constant pressure funnel. Continuously evacuate the tube to maintain a vacuum degree of -0.8 MPa and lower the temperature of the Schlenk tube to -15°C.

[0060] (2) Weigh 3.04 g (0.02 mol) of 1-hexyl-4,5-diethylimidazolium salt and 1.525 g (0.01 mol) of p-chloromethylstyrene, inject the mixture into the Schlenk tube of step (1), and continue stirring for 36 h to allow 1-hexyl-4,5-diethylimidazolium salt to react fully with p-chloromethylstyrene;

[0061] (3) After the reaction is completed, the precipitate is centrifuged and then dried at 80° C. for 6 h to allow the vinyl groups to self-crosslink and form imidazolium salt crystals;

[0062] (4) At 25° C., 5 g of chloromethylated styrene-butylene block copolymer with a styrene content of 57% was weighed and dissolved in 245 g of N-methylpyrrolidone and stirred for 36 h. Then, 0.025 g of N,N,N′,N′-tetramethyl-1,6-hexanediamine was weighed and added and stirred thoroughly to dissolve for 60 s.

[0063] (5) Weigh 0.5 g of imidazolium salt crystals and add them to step (4), stirring at 80° C. for 12 h to obtain a casting solution;

[0064] (6) heating the casting liquid obtained in step (5) in a glass mold at 80° C. for 48 h, and peeling the dried film from the glass plate for later use;

[0065] (7) Weigh 5.0 g of the imidazolium salt crystals prepared in step (3) and add them to 95 g of ethanol to obtain an imidazolium salt ethanol solution with a concentration of 5%;

[0066] (8) The membrane obtained in step (6) is placed in the solution prepared in step (7), soaked for 24 hours, taken out, and repeatedly rinsed with deionized water for 10 times, and then soaked in a 2 mol / L potassium hydroxide solution to fully alkalize for 48 hours, and then taken out and rinsed off the alkaline solution on the surface of the membrane with deionized water, and then thoroughly dried at 80°C for 24 hours to obtain an imidazole crystalline alkaline anion exchange membrane.

[0067] Embodiment 4:

[0068] (1) Weigh 6.99 g (0.01 mol) of MIL-101(Fe) and place it in a Schlenk tube equipped with a constant pressure funnel. Continuously evacuate the tube to maintain a vacuum degree of -1.0 MPa and lower the temperature of the Schlenk tube to -10°C.

[0069] (2) Weigh 3.04 g (0.02 mol) of 1-hexyl-4,5-dimethylimidazolium salt and 0.7625 g (0.005 mol) of p-chloromethylstyrene, inject the mixture into the Schlenk tube of step (1), and continue stirring for 96 h to allow 1-hexyl-4,5-dimethylimidazolium salt to react fully with p-chloromethylstyrene;

[0070] (3) After the reaction is completed, the precipitate is centrifuged and then dried at 60° C. for 8 h to allow the vinyl groups to self-crosslink and form imidazolium salt crystals;

[0071] (4) At 25° C., 2 g of chloromethylated styrene-ethylene-butylene block copolymer with a styrene content of 10% was dissolved in 398 g of N-methylpyrrolidone and stirred for 24 h. Then, 0.002 g of N,N,N′,N′-tetramethylmethanediamine was added and stirred thoroughly for 10 s to dissolve.

[0072] (5) Weigh 0.04 g of imidazolium salt crystals and add them to step (4), stir at 30° C. for 12 h to obtain a casting solution;

[0073] (6) heating the casting liquid obtained in step (5) in a glass mold at 60° C. for 96 h, and peeling the dried film from the glass plate for later use;

[0074] (7) Weighing 1.0 g of the imidazolium salt crystals prepared in step (3) and adding them to 99 g of ethanol to obtain an imidazolium salt ethanol solution with a concentration of 1%;

[0075] (8) The membrane obtained in step (6) is placed in the solution prepared in step (7), soaked for 48 hours, taken out, and repeatedly rinsed with deionized water for 10 times, and then soaked in a 0.1 mol / L sodium hydroxide solution to fully alkalize for 24 hours, and then taken out and rinsed off the alkaline solution on the surface of the membrane with deionized water, and then thoroughly dried at 60°C for 48 hours to obtain an imidazole crystalline alkaline anion exchange membrane.

[0076] Embodiment 5:

[0077] (1) Weigh 6.99 g (0.01 mol) of MIL-101(Fe) and place it in a Schlenk tube equipped with a constant pressure funnel. Continuously evacuate the tube to maintain a vacuum degree of -1.0 MPa and lower the temperature of the Schlenk tube to -10°C.

[0078] (2) Weigh 3.04 g (0.02 mol) of 1-hexyl-4,5-dimethylimidazolium salt and 7.625 g (0.05 mol) of p-chloromethylstyrene, inject the mixture into the Schlenk tube of step (1), and continue stirring for 96 h to allow 1-hexyl-4,5-dimethylimidazolium salt to react fully with p-chloromethylstyrene;

[0079] (3) After the reaction is completed, the precipitate is centrifuged and then dried at 60° C. for 8 h to allow the vinyl groups to self-crosslink and form imidazolium salt crystals;

[0080] (4) At 25° C., 2 g of chloromethylated styrene-ethylene-butylene block copolymer with a styrene content of 10% was dissolved in 398 g of N-methylpyrrolidone and stirred for 18 h. Then, 0.002 g of N,N,N′,N′-tetramethylmethanediamine was added and stirred thoroughly for 100 s.

[0081] (5) Weigh 0.04 g of imidazolium salt crystals and add them to step (4), and continue stirring at 25° C. for 24 h to obtain a casting solution;

[0082] (6) heating the casting liquid obtained in step (5) in a glass mold at 60° C. for 96 h, and peeling the dried film from the glass plate for later use;

[0083] (7) Weighing 1.0 g of the imidazolium salt crystals prepared in step (3) and adding them to 99 g of ethanol to obtain an imidazolium salt ethanol solution with a concentration of 1%;

[0084] (8) The membrane obtained in step (6) is placed in the solution prepared in step (7), soaked for 48 hours, taken out, and repeatedly rinsed with deionized water for 10 times, and then soaked in a 0.1 mol / L sodium hydroxide solution to fully alkalize for 24 hours, and then taken out and rinsed off the alkaline solution on the surface of the membrane with deionized water, and then thoroughly dried at 60°C for 48 hours to obtain an imidazole crystalline alkaline anion exchange membrane.

[0085] Comparative Example 1:

[0086] (1) Weigh 3.04 g (0.02 mol) of 1-hexyl-4,5-dimethylimidazolium salt and 1.525 g (0.01 mol) of p-chloromethylstyrene and inject the mixture into a Schlenk tube. Stir continuously for 96 h to allow 1-hexyl-4,5-dimethylimidazolium salt and p-chloromethylstyrene to react fully.

[0087] (2) After the reaction is completed, the precipitate is centrifuged and then dried at 60° C. for 8 h to allow the vinyl groups to self-crosslink to form an imidazolium salt compound;

[0088] (3) At 25° C., weigh 2 g of chloromethylated styrene-ethylene-butylene block copolymer having a styrene content of 10% and dissolve it in 398 g of N-methylpyrrolidone, then weigh 0.002 g of N,N,N′,N′-tetramethylmethanediamine and add it, stirring thoroughly to dissolve;

[0089] (4) Weigh 0.04 g of an imidazolium salt compound and add it to step (3), and continue stirring at 25° C. for 24 h to obtain a casting solution;

[0090] (5) heating the casting liquid obtained in step (4) in a glass mold at 60° C. for 96 h, and peeling the dried film from the glass plate for later use;

[0091] (6) Weigh 1.0 g of the imidazolium salt compound prepared in step (2) and add it to 99 g of ethanol to obtain an imidazolium salt ethanol solution with a concentration of 1%;

[0092] (7) The membrane obtained in step (5) is placed in the solution prepared in step (6), soaked for 48 hours, taken out, and repeatedly rinsed with deionized water for 10 times, and then soaked in a 0.1 mol / L sodium hydroxide solution to fully alkalize for 24 hours, and then taken out and rinsed off the alkaline solution on the surface of the membrane with deionized water, and then thoroughly dried at 60°C for 48 hours to obtain an imidazole crystalline alkaline anion exchange membrane.

[0093] Comparative Example 2:

[0094] (1) Weigh 6.99 g (0.01 mol) of MIL-101(Fe) and place it in a Schlenk tube equipped with a constant pressure funnel. Continuously evacuate the tube to maintain a vacuum degree of -1.0 MPa and lower the temperature of the Schlenk tube to -10°C.

[0095] (2) Weigh 3.04 g (0.02 mol) of 1-hexyl-4,5-dimethylimidazolium salt and 1.525 g (0.01 mol) of p-chloromethylstyrene, inject the mixture into the Schlenk tube of step (1), and continue stirring for 96 h to allow 1-hexyl-4,5-dimethylimidazolium salt to react fully with p-chloromethylstyrene;

[0096] (3) After the reaction is completed, the precipitate is centrifuged and then dried at 60° C. for 8 h to allow the vinyl groups to self-crosslink and form imidazolium salt crystals;

[0097] (4) At 25° C., weigh 2 g of a chloromethylated styrene-ethylene-butylene block copolymer having a styrene content of 10% and dissolve it in 398 g of N-methylpyrrolidone, stirring thoroughly to dissolve;

[0098] (5) Weigh 0.04 g of imidazolium salt crystals and add them to step (4), and continue stirring at 25° C. for 24 h to obtain a casting solution;

[0099] (6) heating the casting liquid obtained in step (5) in a glass mold at 60° C. for 96 h, and peeling the dried film from the glass plate for later use;

[0100] (7) Weighing 1.0 g of the imidazolium salt crystals prepared in step (3) and adding them to 99 g of ethanol to obtain an imidazolium salt ethanol solution with a concentration of 1%;

[0101] (8) The membrane obtained in step (6) is placed in the solution prepared in step (7), soaked for 48 hours, taken out, and repeatedly rinsed with deionized water for 10 times, and then soaked in a 0.1 mol / L sodium hydroxide solution to fully alkalize for 24 hours, and then taken out and rinsed off the alkaline solution on the surface of the membrane with deionized water, and then thoroughly dried at 60°C for 48 hours to obtain an imidazole crystalline alkaline anion exchange membrane.

[0102] Comparative Example 3:

[0103] (1) Weigh 6.99 g (0.01 mol) of MIL-101(Fe) and place it in a Schlenk tube equipped with a constant pressure funnel. Continuously evacuate the tube to maintain a vacuum degree of -1.0 MPa and lower the temperature of the Schlenk tube to -10°C.

[0104] (2) Weigh 3.04 (0.02 mol) of 1-hexyl-4,5-dimethylimidazolium salt and inject it into the Schlenk tube of step (1), and continue stirring;

[0105] (3) After the reaction is completed, the precipitate is centrifuged and then dried at 60° C. for 8 h to allow the vinyl groups to self-crosslink and form imidazolium salt crystals;

[0106] (4) At 25° C., weigh 2 g of chloromethylated styrene-ethylene-butylene block copolymer having a styrene content of 10% and dissolve it in 398 g of N-methylpyrrolidone, then weigh 0.002 g of N,N,N′,N′-tetramethylmethanediamine and add it, stirring thoroughly to dissolve;

[0107] (5) Weigh 0.04 g of imidazolium salt crystals and add them to step (4), and continue stirring at 25° C. for 24 h to obtain a casting solution;

[0108] (6) heating the casting liquid obtained in step (5) in a glass mold at 60° C. for 96 h, and peeling the dried film from the glass plate for later use;

[0109] (7) Weighing 1.0 g of the imidazolium salt crystals prepared in step (3) and adding them to 99 g of ethanol to obtain an imidazolium salt ethanol solution with a concentration of 1%;

[0110] (8) The membrane obtained in step (6) is placed in the solution prepared in step (7), soaked for 48 hours, taken out, and repeatedly rinsed with deionized water for 10 times, and then soaked in a 0.1 mol / L sodium hydroxide solution to fully alkalize for 24 hours, and then taken out and rinsed off the alkaline solution on the surface of the membrane with deionized water, and then thoroughly dried at 60°C for 48 hours to obtain an imidazole crystalline alkaline anion exchange membrane.

[0111] Comparative Example 4:

[0112] (1) Weigh 6.99 g (0.01 mol) of MIL-101(Fe) and place it in a Schlenk tube equipped with a constant pressure funnel. Continuously evacuate the tube to maintain a vacuum degree of -1.0 MPa and lower the temperature of the Schlenk tube to -10°C.

[0113] (2) Weigh 3.04 g (0.02 mol) of 1-hexyl-4,5-dimethylimidazolium salt and 0.38125 g (0.0025 mol) of p-chloromethylstyrene, inject the mixture into the Schlenk tube of step (1), and continue stirring for 96 h to allow 1-hexyl-4,5-dimethylimidazolium salt to react fully with p-chloromethylstyrene;

[0114] (3) After the reaction is completed, the precipitate is centrifuged and then dried at 60° C. for 8 h to allow the vinyl groups to self-crosslink and form imidazolium salt crystals;

[0115] (4) At 25° C., weigh 2 g of chloromethylated styrene-ethylene-butylene block copolymer having a styrene content of 10% and dissolve it in 398 g of N-methylpyrrolidone, then weigh 0.002 g of N,N,N′,N′-tetramethylmethanediamine and add it, stirring thoroughly to dissolve;

[0116] (5) Weigh 0.04 g of imidazolium salt crystals and add them to step (4), and continue stirring at 25° C. for 24 h to obtain a casting solution;

[0117] (6) heating the casting liquid obtained in step (5) in a glass mold at 60° C. for 96 h, and peeling the dried film from the glass plate for later use;

[0118] (7) Weighing 1.0 g of the imidazolium salt crystals prepared in step (3) and adding them to 99 g of ethanol to obtain an imidazolium salt ethanol solution with a concentration of 1%;

[0119] (8) The membrane obtained in step (6) is placed in the solution prepared in step (7), soaked for 48 hours, taken out, and repeatedly rinsed with deionized water for 10 times, and then soaked in a 0.1 mol / L sodium hydroxide solution to fully alkalize for 24 hours, and then taken out and rinsed off the alkaline solution on the surface of the membrane with deionized water, and then thoroughly dried at 60°C for 48 hours to obtain an imidazole crystalline alkaline anion exchange membrane.

[0120] Comparative Example 5:

[0121] (1) Weigh 6.99 g (0.01 mol) of MIL-101(Fe) and place it in a Schlenk tube equipped with a constant pressure funnel. Continuously evacuate the tube to maintain a vacuum degree of -1.0 MPa and lower the temperature of the Schlenk tube to -10°C.

[0122] (2) Weigh 3.04 g (0.02 mol) of 1-hexyl-4,5-dimethylimidazolium salt and 9.15 g (0.06 mol) of p-chloromethylstyrene and inject the mixture into the Schlenk tube of step (1), and continue stirring for 96 h to allow 1-hexyl-4,5-dimethylimidazolium salt and p-chloromethylstyrene to react fully;

[0123] (3) After the reaction is completed, the precipitate is centrifuged and then dried at 60° C. for 8 h to allow the vinyl groups to self-crosslink and form imidazolium salt crystals;

[0124] (4) At 25° C., weigh 2 g of chloromethylated styrene-ethylene-butylene block copolymer having a styrene content of 10% and dissolve it in 398 g of N-methylpyrrolidone, then weigh 0.002 g of N,N,N′,N′-tetramethylmethanediamine and add it, stirring thoroughly to dissolve;

[0125] (5) Weigh 0.04 g of imidazolium salt crystals and add them to step (4), and continue stirring at 25° C. for 24 h to obtain a casting solution;

[0126] (6) heating the casting liquid obtained in step (5) in a glass mold at 60° C. for 96 h, and peeling the dried film from the glass plate for later use;

[0127] (7) Weighing 1.0 g of the imidazolium salt crystals prepared in step (3) and adding them to 99 g of ethanol to obtain an imidazolium salt ethanol solution with a concentration of 1%;

[0128] (8) The membrane obtained in step (6) is placed in the solution prepared in step (7), soaked for 48 hours, taken out, and repeatedly rinsed with deionized water for 10 times, and then soaked in a 0.1 mol / L sodium hydroxide solution to fully alkalize for 24 hours, and then taken out and rinsed off the alkaline solution on the surface of the membrane with deionized water, and then thoroughly dried at 60°C for 48 hours to obtain an imidazole crystalline alkaline anion exchange membrane.

[0129] Compared with Examples 1-5, no metal organic framework crystal material was added to Comparative Example 1, and no cross-linking agent was added to Comparative Example 2. The alkaline anion exchange membranes of the embodiments and the comparative examples were tested for conductivity and tensile strength, and the results are shown in Table 1. It can be seen from Table 1 that the conductivity and tensile strength of the exchange membrane prepared by the present invention are relatively high, and the effects are better than those of the comparative examples. This is because the imidazolium salt is introduced into the AEMs in two forms, namely, covalent cross-linking and metal organic framework "fixation", which increases the number of functional groups in the membrane, and constructs regular and orderly ion transfer channels with the help of regular lattice structures, reducing ion transfer resistance; at the same time, chloromethylated styrene block copolymers and cross-linking agents are used for cross-linking reactions to form a skeleton structure, thereby improving the stability and mechanical strength of the ion exchange membrane.

[0130] In Comparative Example 1, no metal organic framework crystal material was added, and imidazolium salt was directly added in the preparation of the anion exchange membrane. As the operation time increases, the imidazolium salt will be lost, resulting in a decrease in its performance;

[0131] In the process of preparing the anion exchange membrane in Comparative Example 2, no cross-linking agent was added to the skeleton material, and the skeleton material did not form a cross-linked network structure. On the one hand, the imidazolium salt crystals were not firmly fixed in the skeleton material and were easily lost, resulting in performance impairment. On the other hand, the prepared membrane had poor chemical stability and was easily degraded.

[0132] In Comparative Example 3, only metal organic framework crystal material and imidazolium salt were added. The imidazolium salt entered the micropores of the metal organic framework crystal material, but there was no other compound to fix it, which easily caused the loss of the imidazolium salt, thereby affecting the performance of the polymer membrane. As can be seen from Table 2, its stability is poor.

[0133] The content of p-chloromethylstyrene in Comparative Example 4 is relatively low, and the mechanical strength of the prepared polymer membrane is low. At the same time, the formed quaternary ammonium groups are also relatively small, which affects the ion conduction of the polymer membrane.

[0134] The content of p-chloromethylstyrene in Comparative Example 5 is too high, and the prepared polymer membrane is easily chemically degraded. At the same time, the high content of p-chloromethylstyrene cannot completely enter the cubic structure of the micropores, affecting ion conduction.

[0135] Table 1 Conductivity and tensile strength of anion exchange membrane

[0136] Case <![CDATA[Conductivity / S﹒cm -1 > Tensile strength / MPa Example 1 0.075 25 Example 2 0.080 24 Example 3 0.077 24.1 Example 4 0.095 21 Example 5 0.15 24.7 Comparative Example 1 0.033 19.4 Comparative Example 2 0.074 11.3 Comparative Example 3 0.075 20 Comparative Example 4 0.023 18 Comparative Example 5 0.04 15

[0137] The anion exchange membranes prepared in the examples of the present invention and the comparative examples were immersed in 1.0 mol / L sodium hydroxide solution to perform an alkali stability test, and the results are shown in Table 2. During the preparation of AEMs, the alkali stability of AEMs that were not covalently cross-linked was significantly poor.

[0138] Table 2 Anion exchange membrane quality residual rate test

[0139] Case 30d exchange membrane mass residual rate / % Example 1 98.2 Example 2 98.3 Example 3 98.7 Example 4 93 Example 5 88 Comparative Example 1 72 Comparative Example 2 88 Comparative Example 3 65 Comparative Example 4 64 Comparative Example 5 58

[0140] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. An alkaline anion exchange membrane, characterized in that: It is composed of imidazolium salt crystals, chloromethylated block polymers and crosslinking agents. The imidazolium salt crystals are: a substance formed by using 4,5-disubstituted imidazolium salts and p-chloromethylstyrene as raw materials and fixed in a metal organic framework crystal material; the 4,5-disubstituted imidazolium salt is 1-butyl C4, C5 disubstituted imidazolium salt or 1-hexyl C4, C5 disubstituted imidazolium salt; The molar ratio of the metal organic framework crystal material, 4,5-disubstituted imidazolium salt and p-chloromethylstyrene is 1:2:0.5-5; the chloromethylated block polymer is one or more of chloromethylated styrene-butylene block copolymer (SBS), styrene-ethylene-butylene block copolymer (SEBS), acrylonitrile-butadiene-styrene copolymer (ABS), acrylonitrile-ethylene-styrene copolymer (AES), acrylonitrile-styrene copolymer (AS), acrylonitrile-styrene-acrylate copolymer (ASA), wherein the styrene block content is 10-57wt.%; The cross-linking agent is one or more of N,N,N′,N′-tetramethylmethanediamine (TMMDA), N,N,N′,N′-tetramethylethylenediamine (TMEDA), and N, N, N′, N′-tetramethyl-1, 6-hexanediamine (TMHDA); The C4 and C5 substituents in the 1-butyl C4, C5 disubstituted imidazolium salt or the 1-hexyl C4, C5 disubstituted imidazolium salt are R1 and R2, respectively, and the R1 and R2 are any one of methyl, ethyl, propyl, butyl, isopropyl, and tert-butyl; The imidazolium salt crystal is synthesized by a low-temperature vacuum method.

2. The alkaline anion exchange membrane according to claim 1, characterized in that: The metal organic framework crystal material is a cubic structure with micropores, the pore size of the micropores is 100-1000nm, and the metal organic framework crystal material is one or more of MIL-101 (Fe), MIL-101 (Cr), MIL-53 (Cr), MIL-53 (Fe), ZIF-8, and ZIF-10.

3. The alkaline anion exchange membrane according to claim 1, characterized in that The imidazolium salt crystal is synthesized by a low temperature vacuum method, comprising the following steps: (1) The metal-organic framework material is in a vacuum state; (2) Under low temperature conditions, mixing a mixture of 4,5-disubstituted imidazolium salt and p-chloromethylstyrene with a metal organic framework material and stirring to react; (3) Centrifuge and dry to obtain imidazolium salt crystals.

4. The alkaline anion exchange membrane according to claim 3, characterized in that The vacuum degree of the vacuum state in step (1) is -0.6~-1.0MPa; the low-temperature reaction temperature in step (2) is -20~-10°C, and the stirring time is 48-96h; the precipitate drying temperature in step (3) is 60-100°C, and the drying time is 4-8h; steps (1) and (2) are in the same vacuum state.

5. The alkaline anion exchange membrane according to claim 1, characterized in that The structures of the 1-butyl C4, C5 disubstituted imidazolium salt or the 1-hexyl C4, C5 disubstituted imidazolium salt are as follows: 1-Butyl C4, C5 disubstituted imidazolium salt 1-hexyl C4, C5 disubstituted imidazolium salt.

6. The method for preparing the alkaline anion exchange membrane according to any one of claims 1 to 5, characterized in that: The film-making process includes the following steps: A, dissolving the chloromethylated block polymer in a high boiling point solvent, stirring and dissolving at room temperature to obtain a polymer solution; the high boiling point solvent is one of N-methylpyrrolidone, N,N-dimethylformamide, tetrahydrofuran, and dimethyl sulfoxide; B. Add a crosslinking agent to the polymer solution prepared in step A, and continue to stir and dissolve at room temperature to obtain a mixture solution; C. Weigh imidazolium salt crystals and add them to the mixture solution obtained in step B. Mix and heat to react to obtain a casting solution. D. pouring the casting solution prepared in step C into a glass mold, and peeling the obtained film from the glass mold after drying; E. Soaking the membrane obtained in step D in an ethanol solution of 4,5-disubstituted imidazolium salt; F. Soak the membrane in step E in an alkaline solution, then wash it with deionized water for more than 5 times, and dry it to obtain an imidazole crystal-type alkaline anion exchange membrane.

7. The preparation method according to claim 6, characterized in that: The mass concentration of the polymer solution in step A is 0.5-2wt.%; the amount of the crosslinker added in step B is 0.1-0.5% of the mass of the chloromethylated block polymer; the amount of the imidazolium salt crystal added in step C is 2-10% of the mass of the chloromethylated block polymer; the mass concentration of the 4,5-disubstituted imidazolium salt ethanol solution in step E is 1-5wt%, and the immersion time is 24-48h.

8. The preparation method according to claim 6, characterized in that: The room temperature in step A and step B is 25° C., the stirring time in step A is 24-48 h, the stirring time in step B is 10-120 s, the ultrasonic mixing is performed in step C, the heating temperature is 25-80° C., and the heating reaction time is 0.2-12 h; the drying temperature in step D is 80-100° C., and the drying time is 24-48 h; the drying temperature in step F is 60-80° C., and the drying time is 24-48 h.

9. The preparation method according to claim 6, characterized in that: The alkaline solution in step F is one of sodium hydroxide or potassium hydroxide, the concentration of the alkaline solution is 0.1-2 mol / L, the soaking time is 24-48h, and the drying temperature is 50-60°C.

Citation Information

Patent Citations

  • Cross-linked block polymer anion exchange membrane, preparation method and applications thereof

    CN109384944A

  • Polyether-ether-ketone / cationic metal organic framework cross-linked membrane and preparation method thereof

    CN113078341A